Management Control Systems for J.I.T.: An Empirical Comparison of Japan and the U.S. - Daniel, Shirley J.; Reitsperger, Wolf D. (Journal of International Business Studies, 1991)
Just-in-Time manufacturing (J.I.T.), an essential component of the Japanese manufacturing model, is increasingly emulated by western corporations. While J.I.T. has received considerable conceptual and empirical attention, suitable management control systems, which are essential to successful implementation, have been sorely neglected. This study provides large-scale empirical evidence comparing management control systems as they relate to J.I.T. in the U.S. and Japan.